2017
DOI: 10.1515/helm-2017-0037
|View full text |Cite
|
Sign up to set email alerts
|

First report of multiple anthelmintic resistance in goat farm in Cuba

Abstract: SummaryThis study determined the effi cacies of four classes of anthelmintics (AH) in a goat fl ock where anthelmintic resistance (AR) to ivermectin was suspected. We selected and randomly distributed 105 animals with >500 eggs per gram of feces into seven groups of 15 animals: an untreated control group and groups treated with ivermectin, eprinomectin, albendazole sulfoxide, albendazole, levamisole, and closantel. The goats were individually weighed and treated with the recommended dose. Fecal samples were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In the three screened areas (Nyala: Domaia and Majok, Beleil and Kass) goats positive for an infection with GINs and shedding ≥500 strongyle epg faeces were selected. The cut-off value (≥500 epg) was used according to some previous studies which preferred evaluating anthelmintic resistance in sheep and goats with moderate to highly GINs infection rate [53, 54] and the fact that the precision of the FECR estimate increases with the number of counted eggs [55] which can be more easily achieved using animals with high egg counts. Animals were labelled and grouped into control and treated group based on age class (< 12 months old and ≥ 1 years old), followed by epg (500–1000, 1000–2000, 2000–3000, …) within each age class.…”
Section: Methodsmentioning
confidence: 99%
“…In the three screened areas (Nyala: Domaia and Majok, Beleil and Kass) goats positive for an infection with GINs and shedding ≥500 strongyle epg faeces were selected. The cut-off value (≥500 epg) was used according to some previous studies which preferred evaluating anthelmintic resistance in sheep and goats with moderate to highly GINs infection rate [53, 54] and the fact that the precision of the FECR estimate increases with the number of counted eggs [55] which can be more easily achieved using animals with high egg counts. Animals were labelled and grouped into control and treated group based on age class (< 12 months old and ≥ 1 years old), followed by epg (500–1000, 1000–2000, 2000–3000, …) within each age class.…”
Section: Methodsmentioning
confidence: 99%
“…For example, resistance of GINs to one or more anthelmintic classes in goats has so far been described in many European countries including Great Britain [10], the Netherlands [11], Spain [12], Italy [13], Lithuania [14], France [15,16], Switzerland [17], Denmark [18], Norway [19], Germany [20], Slovakia [21], Czech Republic [22], and Poland [7,[23][24][25]. The situation is similar in goat herds outside of Europe as described in USA [26], South Africa [27], Kenya [28], Cuba [29], Malaysia [30], India [31], Australia [32], and New Zealand [33].…”
Section: Introductionmentioning
confidence: 74%
“…Chemoresistance is a concern in the management of gastrointestinal helminths [ 8 , 9 , 10 ]. This phenomenon has been recognized for more than 50 years [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in this regard, in 2010, in Brazil, Alfredo et al confirmed helminth chemoresistance to several substances such as Levamisole, Moxidectin, Albendazole, Ivermectin, Nitroxinil, Disophenol, Trichlorfon, and Closantel following tests conducted on a flock of 5000 sheep [ 12 ]. Similarly, chemoresistance to ivermectin has been confirmed in several areas of the world, such as Europe [ 13 ], Cuba [ 8 ], or Argentina [ 9 ].…”
Section: Introductionmentioning
confidence: 99%